Apathetic Thyrotoxicosis – a rare diagnosis - Correia, Ana (2005)
A 67-year-old male patient was admitted because of unexplained weight loss, apathy and lethargy. He had a prior history of degenerative aortic valve disease and heart failure. A mechanical prosthetic aortic valve was implanted.During the investigation the clinical exams and the laboratory fi ndings lead to the diagnosis of apathetic thyrotoxicosis. This entity is found mainly in the elderly population in which the usual hyperkinetic presentation is replaced by apathy, inactivity, tiredness and lack of reaction to the stress.